2021
DOI: 10.1080/00224499.2021.1912692
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Transgender and Cisgender Experiences of Being Taken Advantage of Sexually While Under the Influence of Alcohol and/or Other Drugs

Abstract: A small body of literature suggests that transgender people are more frequently exposed to sexual violence while they are under the influence of alcohol than cisgender counterparts. The goal of this study was to report any differences between transgender (n = 1,136) and cisgender (n = 74,277) respondents to the Global Drug Survey on their experiences of being taken advantage of sexually while under the influence of alcohol and/or other drugs. We found that transgender people were more likely than cisgender peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Our results were consistent with our hypothesis that stigma specific to TGD individuals leads to increased substance use (count score of hazardous drinking and the use of up to 10 drugs to get high) and HIV sexual risk behaviors (condomless sex, multiple partners, or sex work) and corroborate prior research. 5,19–-22,52 Counter to our hypothesis, TGD-related stigma was positively associated with the use of HIV prevention clinical services indirectly through substance use and HIV sexual risk behaviors. TGD-related stigma in itself does not lead to improved access to HIV prevention services.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our results were consistent with our hypothesis that stigma specific to TGD individuals leads to increased substance use (count score of hazardous drinking and the use of up to 10 drugs to get high) and HIV sexual risk behaviors (condomless sex, multiple partners, or sex work) and corroborate prior research. 5,19–-22,52 Counter to our hypothesis, TGD-related stigma was positively associated with the use of HIV prevention clinical services indirectly through substance use and HIV sexual risk behaviors. TGD-related stigma in itself does not lead to improved access to HIV prevention services.…”
Section: Discussionmentioning
confidence: 77%
“…7,[15][16][17][18] TGD individuals may use substances to cope with discrimination and interpersonal stressors. 6,[19][20][21][22][23] Similarly, national data indicate that HIV infection prevalence estimates among TGD individuals range from 9.1% based on laboratory-confirmed tests to 16.1% based on self-reported data compared with 0.3% of the general population with laboratoryconfirmed tests. 10,15,24 Stigma and discrimination have also been linked to increased HIV sexual risk behaviors among TGD populations, such as sex work and condomless sex.…”
mentioning
confidence: 99%
“…Transgender and gender diverse (TGD) people experience higher rates of traumatic victimization compared with cisgender people (non-TGD people whose gender is concordant with their sex assigned at birth; Connolly et al, 2021; Flores et al, 2021). Consequently, rates of posttraumatic stress disorder (PTSD) and other trauma-related psychiatric disorders are elevated among TGD samples (Livingston et al, 2022; McDowell et al, 2019).…”
mentioning
confidence: 99%
“…The 2015 US Transgender Survey found that 10% of transgender and gender minority persons reported past year assault, and nearly half (47%) reported any lifetime sexual assault (James et al, 2016). In a recent analysis of data from the Global Drug Survey, Connolly et al (2021) reported that transgender persons were more likely to have experienced substance-facilitated sexual assault (colloquially referred to as "being taken advantage of" while using substances) than cisgender persons, and some populations within the trans umbrella (e.g., nonbinary persons, trans-masculine persons assigned female sex at birth) may experience even higher prevalence of victimization than other trans peers.…”
mentioning
confidence: 99%
“…A systematic review of studies with population-based or census studies by Rothman et al (2011) provides median estimates of lifetime sexual assault victimization among gay and bisexual men (30%) and lesbian and bisexual women (43%) in the United States. Within the SGM spectrum, transgender and nonbinary persons report even higher rates of sexual violence victimization (Atteberry-Ash et al, 2019; Connolly et al, 2021; Griner et al, 2020). For example, Coulter et al (2017) report that about 21% of transgender undergraduate students had experienced past-year sexual assault, compared to about 4% of cisgender men and 9% of cisgender women.…”
mentioning
confidence: 99%